Reconfigurable EIT Metasurface with Low Excited Conductivity of VO2 - Ruijie Li; Qiang Feng; Gaomou Lei; Qifan Li; Haixia Liu; Peng Xu; Jiaqi Han; Yan Shi; Long Li (Photonics)
The active materials-loaded reconfigurable metasurface is a potential platform for terahertz (THz) communication systems. However, the requirements of the modulation performance and the modulation rate put forward the opposite requirements on the excited conductivity of active materials. In this paper, we proposed a concept for a metal-doped active material switch that can produce an equivalent high excited conductivity while reducing the required threshold of the active material conductivity, thus balancing the conflict between the two mutual requirements. Based on it, we designed a reconfigurable electromagnetically induced transparency (EIT) metasurface driven by a low excited conductivity of vanadium dioxide <semantics><mfenced separators="" open="(" close=")">VO2</mfenced></semantics>, which can achieve the amplitude modulation and amplitude coding under the control of light and electric. Simulation results validate the role of the metal-doped <semantics>VO2</semantics> switch on the metasurface. This work provides a new scheme to mediate the contradiction between the modulation performance and the modulation rate in the requirement of active material’s excited conductivity, which facilitates the development of new terahertz modulators based on reconfigurable metasurfaces. In addition, the concept of a metal-doped active material switch will also provide a solution to the limitations of active material from the design layer.